2001
DOI: 10.1111/j.1755-0238.2001.tb00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil nitrogen utilisation for growth and gas exchange by grapevines in response to nitrogen supply and rootstock

Abstract: This study investigated the response to nitrogen (0 or 100 kg N/ha) of field-grown Müller-Thurgau grapevines grafted on six rootstocks (Kober 5BB, Teleki 5C, Teleki 8B, Selection Oppenheim 4, Couderc 3309, Ruggeri 140). Half the nitrogen was applied four weeks pre-flowering and half at the end of flowering. Glutamine accounted for over 85% of xylem nitrogen, indicating that most soil nitrogen was assimilated by way of vine root metabolism. Nitrogen supply increased the translocation of glutamine, glutamate, NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 15 publications
7
72
0
Order By: Relevance
“…The action of N, P and K increased the thickness of canes which could be attributed to their effect on accumulation of carbohydrates and protein as well as on their role in the formation of cellulose and lignin [34]. Also, increasing rate of N considerably increased cane thickness of 'Red Roomy' grapevine [35].…”
Section: Resultsmentioning
confidence: 99%
“…The action of N, P and K increased the thickness of canes which could be attributed to their effect on accumulation of carbohydrates and protein as well as on their role in the formation of cellulose and lignin [34]. Also, increasing rate of N considerably increased cane thickness of 'Red Roomy' grapevine [35].…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism for grapevine scion vigor controlled by rootstocks is poorly understood, several authors have shown effects on water relations (Souza et al, 2009), gas exchange (Soar et al, 2006), vegetative vigor (Keller et al, 2001), yield and grape quality (Nuzzo and Mathews, 2006). Therefore, the selection of an appropriate rootstock may provide a powerful tool for managing the growth and fruiting of grapevine scions subjected to the double pruning technique.…”
Section: Introductionmentioning
confidence: 99%
“…Rootstocks are also used for their resistance to or tolerance of nematodes, adverse soil conditions such as drought, waterlogging, high or low pH, or salinity, and their ability to influence vine vigor and fruit ripening (Currle et al 1983, Pongrácz 1983, Galet 1998, Whiting 2004. Although the compounds responsible for fruit composition are mostly determined by the genotype of the scion (e.g., Gholami et al 1995), rootstocks may alter fruit composition indirectly by influencing scion vigor, canopy configuration, yield formation, and nutrient uptake (Schumann 1974, Ruhl et al 1988, Keller et al 2001a, 2001b.…”
mentioning
confidence: 99%